2015
DOI: 10.1152/ajpcell.00176.2014
|View full text |Cite
|
Sign up to set email alerts
|

The inward rectifier potassium channel Kir2.1 is expressed in mouse neutrophils from bone marrow and liver

Abstract: Neutrophils are phagocytic cells that play a critical role in innate immunity by destroying bacterial pathogens. Channels belonging to the inward rectifier potassium channel subfamily 2 (Kir2 channels) have been described in other phagocytes (monocytes/macrophages and eosinophils) and in hematopoietic precursors of phagocytes. Their physiological function in these cells remains unclear, but some evidence suggests a role in growth factor-dependent proliferation and development. Expression of functional Kir2 cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(11 citation statements)
references
References 68 publications
(115 reference statements)
1
10
0
Order By: Relevance
“…Finally, a dose-response curve for ML133 block was constructed and yielded an IC 50 of 3.5 μM ( n = 4–7 cells for each point, Figure 1F ). This value is comparable to the reported values in HEK cells (Wang et al, 2011 ) and murine neutrophils (Masia et al, 2015 ).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…Finally, a dose-response curve for ML133 block was constructed and yielded an IC 50 of 3.5 μM ( n = 4–7 cells for each point, Figure 1F ). This value is comparable to the reported values in HEK cells (Wang et al, 2011 ) and murine neutrophils (Masia et al, 2015 ).…”
Section: Resultssupporting
confidence: 91%
“…ML133 is a recently identified small molecule inhibitor of the Kir2-family, and it blocks Kir2.1 heterologously expressed in HEK cells with an IC 50 of 1.8 μM at 7.4 pH (less effective at lower pH; Wang et al, 2011 ). Very few studies have used ML133 (Wang et al, 2011 ; Masia et al, 2015 ), and it has not been reported for microglia.…”
Section: Resultsmentioning
confidence: 99%
“…For this, we designed an extracellular solution that mimics the ionic composition of the cytosol, and causes minimal interference with the expected behavior of the sensor. The solution where glucose was applied contained physiological concentrations of K + , Na + and Cl − (Alberts et al, ), along with gluconate as the major anion (Lutas, Birnbaumer, & Yellen, ; Masia, Krause, & Yellen, ). Free Mg 2+ concentration was adjusted within the range of physiological values (Romani & Scarpa, ) and free Ca 2+ was buffered at ~80 nM, which is close to the Ca 2+ concentration at rest in HEK293 cells (Tong, McCarthy, & MacLennan, ), and neurons (Grienberger & Konnerth, ).…”
Section: Methodsmentioning
confidence: 99%
“…, along with gluconate as the major anion (Lutas, Birnbaumer, & Yellen, 2014;Masia, Krause, & Yellen, 2015). Free Mg 2+ concentration was adjusted within the range of physiological values (Romani & Scarpa, 1992) and free Ca 2+ was buffered at ~80 nM, which is close to the Ca 2+ concentration at rest in HEK293 cells (Tong, McCarthy, & MacLennan, 1999), and neurons (Grienberger & Konnerth, 2012).…”
mentioning
confidence: 99%
“…Sensitivity to intracellular acidification is not a well-documented feature of K IR 2.1 as it is for other K IR and K 2P channels (35,36). We therefore tested whether heterologously expressed K IR 2.1 channels could be blocked by intracellular acidification.…”
Section: Sour Taste Cells Respond To Intracellular Acidification Withmentioning
confidence: 99%